Determinants of Business Resilience and Sustainable Performance - Indarto; Budiati, Yuli; Lestari, Rohmini Indah; Prawihatmi, Catharina Yekti (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
This study examines how corporate social responsibility (CSR) affects sustainable performance and business resilience using stakeholder relationships and innovation capacity as mediating variables. Structural Equation Modeling (SEM) with a Partial Least Square technique is used for data analysis. The sampling method used a purposive method with a total sample of 151 people. A systematic questionnaire was used to gather primary data. According to the study's findings, stakeholder connections and innovative ability have been directly and positively impacted by corporate social responsibility. Stakeholder relationships having the ability to innovate positively impacts the resilience of businesses. Meanwhile, relationships between stakeholders and innovation capacity influence sustainable performance, mediated by business resilience. The theoretical implication of this research is that CSR will increase business resilience and sustainable performance if CSR can create relationships between stakeholders and innovation capacity.